2021
DOI: 10.18203/2349-2902.isj20214755
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of plasma D-dimer levels with breast carcinoma

Abstract: Background: Breast cancer is the most commonly occurring cancer in women. There is a correlation between cancer and hyper coagulation. Carcinoma increases the level of cross-linked fibrin degradation product (plasma D-dimer), indicative of systemic activation of fibrinolysis, hemostasis and angiogenesis. This study attempted to correlate raised plasma D-dimer in breast cancer.Methods: A retrospective study was conducted in the department of general surgery in GCS hospital, Ahmedabad where in patients admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There was no significant relationship with tumour size and histopathological grade of tumour. 2 In a small prospective study of 70 patients (35 diagnosed with breast cancer and 35 with benign breast disease), Ghadhban et al showed that baseline DD level was normal (<.25) mg/l in 97.1% of patients with benign breast disease, but it was elevated in 88.6% of breast cancer patients. DD concentration was correlated with tumour size and grade, lympho-vascular invasion, and lymph nodes involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant relationship with tumour size and histopathological grade of tumour. 2 In a small prospective study of 70 patients (35 diagnosed with breast cancer and 35 with benign breast disease), Ghadhban et al showed that baseline DD level was normal (<.25) mg/l in 97.1% of patients with benign breast disease, but it was elevated in 88.6% of breast cancer patients. DD concentration was correlated with tumour size and grade, lympho-vascular invasion, and lymph nodes involvement.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Breast cancer (BC) is the most frequently recognised neoplastic disease in women, with an estimated 2.3 million new cases diagnosed annually. 2 The number of BC diagnosed worldwide has been increasing at an alarming rate in the last decades. 3 Thus, many efforts are made to detect cancer cells or their products on molecular level, and especially, to find the molecular and/or biological predictors of treatment relapse and worse survival.…”
Section: Introductionmentioning
confidence: 99%